2000
DOI: 10.1086/301554
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Cold Dust in Orion A and B

Abstract: Large scale far-infrared (FIR) observations of the Orion complex at 205 and 138 µm are presented with an aim of studying the distribution of cold (<25 K) dust. The maps in these FIR bands extend over ∼3600 sq. arcmin and cover regions around OMC-1, 2, 3 in Orion A and NGC 2023 and NGC 2024 in Orion B. Some limited regions have also been mapped at 57 µm. A total of 15 sources in Orion A and 14 in Orion B (south) have been identified from our FIR maps. Dust temperature distribution in both Orion A and Orion B (s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 22 publications
3
33
2
Order By: Relevance
“…This makes identification of discrete sources and photometry in the mid-infrared difficult. The physical appearance of the region in the mid-infrared differs quite significantly from the structures seen in low resolution IRAS and far-infrared data (Mookerjea et al 2000), the moderate resolution 1.3 mm data (Launhardt et al 1996) and the sub-mm SCUBA data presented here. In the far-infrared wavelengths the Table 3 and the open squares denote the location of the free-free emission sources VLA 1-3 (Reipurth et al 2004). emission is from the HD 37903 and the bright sources directly to the south of it.…”
Section: Large Scale Overview Of the Ngc2023contrasting
confidence: 54%
“…This makes identification of discrete sources and photometry in the mid-infrared difficult. The physical appearance of the region in the mid-infrared differs quite significantly from the structures seen in low resolution IRAS and far-infrared data (Mookerjea et al 2000), the moderate resolution 1.3 mm data (Launhardt et al 1996) and the sub-mm SCUBA data presented here. In the far-infrared wavelengths the Table 3 and the open squares denote the location of the free-free emission sources VLA 1-3 (Reipurth et al 2004). emission is from the HD 37903 and the bright sources directly to the south of it.…”
Section: Large Scale Overview Of the Ngc2023contrasting
confidence: 54%
“…Early 2.2 m observations of a large part of the molecular cloud made by Lada et al (1991b) identified four embedded star clusters, and subsequent wide-field imaging of the stellar component is available via the Two Micron All Sky Survey (2MASS) images (Carpenter 2000). The distribution of relatively warm dust was mapped by the Infrared Astronomical Satellite (IRAS ), although for our purposes with limited angular resolution, and in far-infrared emission at 138 and 205 m ( Mookerjea et al 2000). The molecular component has been surveyed by a number of authors, e.g., Miesh & Bally (1994) in the 13 CO J ¼ 1-0 transition and by Kramer et al (1996) with lower angular resolution in the 13 CO and 12 CO J ¼ 2-1 and 3-2 transitions.…”
Section: Introductionmentioning
confidence: 99%
“…From a comparison of the two temperature maps of figure 4, two differences are found: (1) the dust temperature T(60/100) derived from the two IRAS bands is, on an average, 10 Kelvin higher than T LG and (2) the T(60/100) map (figure 4b) shows the same spurious-pattern as seen in the IRAS 100 µm map. Mookerjea et al (2000) presented a dust temperature map derived from their 138 and 205 µm intensities around Orion KL neighborhood and northern ridge. However, because their temperature map covers too small an area, a comparison with the present work is not meaningful.…”
Section: Dust Temperature and Optical Depthmentioning
confidence: 99%
“…Previous investigations successfully revealed the dust distribution of this region, but covered only a part of the ISF-OMC-1 and its vicinity, OMC-2, and OMC-3. Mookerjea et al (2000) mapped this region at 138 and 205 µm with a spatial resolution of 1.…”
Section: Introductionmentioning
confidence: 99%